Faktor-faktor Penyebab Perilaku Membolos dan Implikasinya dalam Bimbingan dan Konseling di SMK Negeri 6 Padang - Abdussalam, Hazel; Neviyarni, Neviyarni (AHKAM, 2025)
This research was motivated by the problems of students in vocational high schools, especially at SMK Negeri 6 Padang, namely that students were found to be engaging in truant behavior caused by various factors, both internal and external. Internal factors include oneself and family, while external factors include school and society. The factors that cause truant behavior really need to be known by various parties. The role of schools, guidance and counseling teachers and parents plays a very important role in overcoming students' truant habits. This research aims to describe the factors that cause students' truant behavior at SMK Negeri 6 Padang City and describe the implications for Guidance and Counseling (BK) teachers in preventing and handling it. This research uses a qualitative approach with a case study method. Data collection was carried out through in-depth interviews with 3 students who had the habit of skipping classes and 1 guidance counselor, as well as 1 homeroom teacher and 3 parents as additional informants in this research. Apart from that, direct observations were also made of students and BK teachers during interviews. Data analysis in this research was carried out in three stages, namely data reduction, data exposure, and conclusion drawing and verification. The results of the research show that there are four main factors that cause students' truant behavior, namely school factors, self-factors, family factors, and community factors. The implication in guidance and counseling is providing information services in the form of material delivered via media in the form of videos about preventing truancy behavior, then the guidance and counseling teacher provides individual counseling services and group counseling services.